Pharmacognostic Standardization, Extraction, Isolation, and Spectroscopic Characterization of L-DOPA from Mucuna pruriens Seeds - Roshan, Asha; Chandra Sharma, Vikas (Journal of Neonatal Surgery, 2025)
ABSTRACT Mucuna pruriens (L.) DC., a revered Ayurvedic legume, is a potent source of L-DOPA, a key therapeutic for neurological disorders. This study establishes standardized protocols for its pharmacognostic evaluation, extraction, isolation, and characterization of L-DOPA from seeds. Seeds sourced from Madhya Pradesh, India, underwent macroscopic (reniform, black, 12.34 ± 0.21 mm × 9.87 ± 0.18 mm) and microscopic analyses (lignified macrosclereids, no starch grains), confirming authenticity per Ayurvedic Pharmacopoeia standards. Physicochemical parameters (foreign matter: 0.32% w/w; moisture: 6.85% w/w; water-soluble extractive: 18.76% w/w) ensured quality. Acidified ethanolic extraction (1:1 ethanol-water, 0.1% citric acid) yielded a 12.5% w/w crude extract (MPE), rich in polar bioactives. Column chromatography isolated a crystalline compound (MP-01, 0.85% w/w from EAF), identified as L-DOPA via FTIR (3400–3200 cm⁻¹ OH/NH), HR-ESI-MS (m/z 198.0763 [M+H]⁺), and ¹H/¹³C NMR. These protocols address variability in phytochemical content, ensuring reproducibility and regulatory compliance. The findings position M. pruriens as a sustainable L-DOPA source for Parkinson’s and depression management, supporting its ethnomedicinal legacy and warranting further clinical and industrial exploration.